2017
DOI: 10.21474/ijar01/3568
|View full text |Cite
|
Sign up to set email alerts
|

Ip-10 as a Predictor of Treatment Response in Chronic Hepatitis C Patients.

Abstract: Background & Aim: Hepatitis C virus (HCV) is a globally prevalent pathogen and a leading cause of death and morbidity. IFN-gamma inducible protein 10 kDa (IP-10, or CXCL10), predict a more pronounced first phase decline of HCV RNA during anti-viral therapy. We assessed pretreatment serum IP-10 as a predictor of SVR in treated chronic HCV. Subjects and methods: Seventy adult chronic HCV patients were included in the prospective controlled study and 10 healthy subjects as a control group. All patients were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Mi-RNAs, short, non-coding RNAs that regulate gene expression, have been associated with histological features of NAFLD and are readily detected in the circulation. [31][32][33][34][35] The current study showed a significant increase in the level of mi-RNA-122 in NAFLD patients compared to controls, and its level is associated with disease severity from simple steatosis to steatohepatitis. This finding is in agreement with Jampoka et al, 36 who found that serum mi-RNA-122 levels in NAFLD patients were significantly higher than those found in the control group.…”
Section: Discussionmentioning
confidence: 96%
“…Mi-RNAs, short, non-coding RNAs that regulate gene expression, have been associated with histological features of NAFLD and are readily detected in the circulation. [31][32][33][34][35] The current study showed a significant increase in the level of mi-RNA-122 in NAFLD patients compared to controls, and its level is associated with disease severity from simple steatosis to steatohepatitis. This finding is in agreement with Jampoka et al, 36 who found that serum mi-RNA-122 levels in NAFLD patients were significantly higher than those found in the control group.…”
Section: Discussionmentioning
confidence: 96%